USING LANDSAT IMAGERIES FOR PARTICLE POLLUTION MAPPING IN HANOI CITY - Thi Thuy An, Thai; Tien Lam, Ly; Hai Hoa, Nguyen; Thai Son, Le; Van Hung, Nguyen (Journal of Forestry Science and Technology, 2018)
Recently, particulate matter (PM) is a serious problem in terms of air pollution in Hanoi, Vietnam. For particle pollution mapping in Hanoi city, the study used Landsat images which were captured in 2011, 2015 and 2017 with practically monitoring data of suspended particle concentration at the same points of time. By using vegetation indices calculated from Landsat images, we generated maps of Air Pollution Index (API) that has been used as a simple and generalized way to describe air quality. Mapped APIs were extracted to compare with the corresponding practical APIs calculated from monitoring data station. The results showed that these APIs had significant similarities. In addition, particle pollution in Hanoi city was at heavily polluted level, especially in surroundings of populous areas, such as Vinhomes Village, Times City, Trung Hoa Ward of Cau Giay district, and main roads as Tran Duy Hung street and Nguyen Van Cu street. The results of the study provide additional data contributing to air pollution monitoring, evaluation and prediction that support to solutions to reduce negative impacts of suspended particles on the environment and public health.